How the carbon emissions trading system affects green total factor productivity? A quasi-natural experiment from 281 Chinese cities - Shao, Wei; Yang, Ke; Jin, Zebin (Frontiers in Energy Research, 2023)
China’s emissions trading system is often cited as a model for developing countries using market-based means to solve pollution problems, but few have objectively assessed the solution from a productivity perspective. Therefore, in this study, the green total factor productivity (GTFP) of 281 prefecture-level cities was calculated by the DEA-Malmquist method, and the policy effects were evaluated by setting quasi-natural experiments. The results show that: Carbon emissions trading system has a positive contribution to GTFP; When facing a more compatible carbon trading system, enterprises will choose two paths: innovation compensation and industrial upgrading to improve GTFP, so as to get rid of the cost constraints caused by carbon emission control; The policy effect of carbon emission trading system varies significantly in different regions. In the economically developed eastern region, the effect of policy implementation is relatively significant, while the effect of policy implementation in the western region is not significant; Further analysis shows that as a market-based environmental policy, the incentive effect of carbon trading system needs to rely on a perfect market system. This study provides empirical evidence and policy enlightenment for developing countries to build and improve emission trading system.